BIOLOGICALLY ACTIVE FOOD ADDITIVES FROM LOCAL AMARANTH VARIETIES GROWING IN UZBEKISTAN - N. Tukhtaboev; N. Ismoilova; Sh. Khoshimjonov; G. Kosimova (Scholars Digest Publishing, 2023)
The purpose of this work is to evaluate the commercial indicators of biologically active food additives obtained from local varieties of amaranth based on organoleptic, physicochemical indicators, requirements for raw materials.
Keywords: dietary supplements, amaranth, food additives, tablet, capsule, powder, technical requirements, packaging, labeling, control methods.